Ekspertinės sistemos ir įvertinimai - Broniukaitis, Romualdas (Information & Media, 1996)
The essence of expertise systems (ES) - put into system the expert's knowledge and use it multiply without the expert's participation.In its essence this is an intellectual programme that may draw reasonable conclusions on the grounds of the knowledge in any specific field of cognition. This system solves the tasks that in other case would be impossible to solve without the expert's assistance.Each examination is conducted specifically and raises different issues, although simple elementary operations exist that are used in various examinations. In the meantime a set of typical tasks is distinguished that are solved by using expertise systems. Their use produces great effect. One of the first problems solved by using ES was interpretation tasks.Interpretation is data analysis aiming to establish its essence.Diagnosis means establishment of failures and shortages in equipment or complex systems that is based on data interpretation. Requirements for making diagnosis are the same as for interpretation.Monitoring (control) is a regular fixing of signals and presentation of messages in case of the situation that needs interference. On the whole, this is a part of diagnostic system.Forecasting means prediction of future events on the grounds of past material.Planning means drafting of certain action programme.ES are also classified in accordance with the types of tasks.